1986
DOI: 10.1056/nejm198601163140302
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Serum Lipoprotein Levels and Systolic Blood Pressure to Early Atherosclerosis

Abstract: We assessed the relation of risk factors for cardiovascular disease to early atherosclerotic lesions in the aorta and coronary arteries in 35 persons (mean age at death, 18 years). Aortic involvement with fatty streaks was greater in blacks than in whites (37 vs. 17 percent, P less than 0.01). However, aortic fatty streaks were strongly related to antemortem levels of both total and low-density lipoprotein cholesterol (r = 0.67, P less than 0.0001 for each association), independently of race, sex, and age, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
109
0
10

Year Published

1989
1989
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 946 publications
(135 citation statements)
references
References 28 publications
6
109
0
10
Order By: Relevance
“…Previous studies by Schrott et al (1982) and Moll et al (1983) showed that children and adolescents with elevated LDL-cholesterol often come from families with a high incidence of coronary heart disease. This fact reinforces the importance of LDL-cholesterol determination in adolescence and of autopsy studies performed in children and young people (Newman, 1986), which have indicated that the fatty streaks in the aorta are also directly related to this part of the lipid profile. Thus, by determining the levels of LDLc, it is possible to detect family risks early, and interventions can be implemented before the occurrence of coronary events.…”
Section: Atherosclerosissupporting
confidence: 81%
“…Previous studies by Schrott et al (1982) and Moll et al (1983) showed that children and adolescents with elevated LDL-cholesterol often come from families with a high incidence of coronary heart disease. This fact reinforces the importance of LDL-cholesterol determination in adolescence and of autopsy studies performed in children and young people (Newman, 1986), which have indicated that the fatty streaks in the aorta are also directly related to this part of the lipid profile. Thus, by determining the levels of LDLc, it is possible to detect family risks early, and interventions can be implemented before the occurrence of coronary events.…”
Section: Atherosclerosissupporting
confidence: 81%
“…An argument for limiting fat intake in children is that atherogenesis is a lifelong process, and may be accelerated by a high-fat diet due to its effect on blood lipid levels. Post-mortem studies have shown that the relationship between blood lipid levels and the extent of atherosclerotic lesions is already present in childhood (Newman et al, 1986;Berenson et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…For example, fatty streaks (the presumed precursor to atherosclerotic plaques) in adolescence are correlated with serum cholesterol and blood pressure in this population, and fibrous plaques characteristic of atherosclerosis become evident by age 20 (Newman et al, 1986). Moreover, blood pressure in the high-normal range in adolescence is a strong predictor of adult hypertension (Shear, Burke, Freedman, & Berenson, 1986).…”
Section: Morbidity and Mortality In Adolescencementioning
confidence: 99%